2014
DOI: 10.5897/ajmr2013.6517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of different enterococcal species isolated from blood and their susceptibility to antimicrobial drugs in Vojvodina, Serbia, 2011-2013

Abstract: Enterococci are one of the leading causes of nosocomial infections worldwide. Enterococcus faecalis and Enterococcus faecium are the most commonly isolated. The aim of this study was to determine prevalence of these species isolated from blood samples of hospitalized patients and their susceptibility to antibiotics particularly to vancomycin and high concentrations of aminoglycosides. A total of 89 enterococcal strains isolated from blood samples between January 1 st 2011 and August 31 st 2013 were tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
2
5
1
Order By: Relevance
“…The current study showed that 22.7% of the isolates were resistant to vancomycin which is comparable with finding from Tabriz in Iran [ 29 ] and Mansoura in Egypt [ 28 ], but higher than the prevalence reported from Turkey, 1.55% [ 30 ]; 10% [ 31 ] and 16% [ 32 ] from Iran. But lower than the findings from Serbia, 54% [ 33 ]; Iran [ 34 ] and Nigeria, 42.9% [ 20 ] in clinical isolates from all age groups. The increased prevalence of VRE infection in our study might be associated with the availability and use of vancomycin in Jimma Specialized Hospital.…”
Section: Main Textcontrasting
confidence: 58%
“…The current study showed that 22.7% of the isolates were resistant to vancomycin which is comparable with finding from Tabriz in Iran [ 29 ] and Mansoura in Egypt [ 28 ], but higher than the prevalence reported from Turkey, 1.55% [ 30 ]; 10% [ 31 ] and 16% [ 32 ] from Iran. But lower than the findings from Serbia, 54% [ 33 ]; Iran [ 34 ] and Nigeria, 42.9% [ 20 ] in clinical isolates from all age groups. The increased prevalence of VRE infection in our study might be associated with the availability and use of vancomycin in Jimma Specialized Hospital.…”
Section: Main Textcontrasting
confidence: 58%
“…This result was in line with a finding in Nigeria 42.9% [17]; but lower than in Iraq 71.4% [27] and Serbia 54.05% [28]. This discrepancy might be due to the difference in type of clinical samples analyzed as it was on urine in the case of Iraq and blood in case of Serbia.…”
Section: Discussionsupporting
confidence: 89%
“…This variation might be due to difference in the study participants and type of specimen which was only hospitalized patients with UTI in the previous study. This study also revealed that, 33.3% of enterococci isolates developed resistance to all tested antibiotics which was almost similar with report from Nigeria 42.86% [28]. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to the report of the National Reference Laboratory for Antimicrobial Monitoring and Surveillance, Serbia belongs to a group of European countries with the highest rates of resistance [1, 2]. …”
Section: Introductionmentioning
confidence: 99%